Comparing conservative and surgical approaches for the treatment of iliotibial band syndrome - Bezerra, Cristian Erik Campos; Dias, Heike Felipe Rangel; Peixoto, Virginia Garcia; Schmidt , Maria Clara Berger; Tomaz, Heloisa Brandão Muniz; Segatto, Rodrigo Simitan; Silva, Thatiane Leite da; Solidade, Cassio Humberto Rocha; Junior, Lúzio Zelles de Alencastro; Contiero , Marcelo (Seven Editora, 2023)
Introduction: This research work focuses on comparing conservative and surgical approaches for the treatment of Iliotibial Band Syndrome (ITBS). Objective: The aim of this research work is to compare conservative and surgical approaches for the treatment of ITBS, examining their efficacy, risks, and benefits. Methodology: This article presents a systematic literature review on the efficacy, safety, and cost-effectiveness of treatment approaches for Iliotibial Band Syndrome (ITBS). The research involved searching scientific databases to identify relevant studies addressing these aspects. The selected studies were analyzed for their results on the efficacy, safety, and cost-effectiveness of conservative and surgical approaches for ITBS. Data analysis was conducted descriptively and interpretively, highlighting efficacy differences between approaches, factors influencing efficacy and safety, and evaluating the cost-effectiveness of the approaches. The article discusses the results of the selected studies in relation to the research objectives, emphasizing their limitations. Discussion: Throughout the work, a comparative analysis of conservative and surgical treatment approaches for Iliotibial Band Syndrome (ITBS) conducted in this research highlights the efficacy, safety, and cost-effectiveness of both treatment modalities. The study found that conservative treatments for ITBS were not effective, making surgical treatment the preferred option for long-term pain relief. Results: The article suggests that early surgical treatment is the optimal choice, especially for younger patients, as outcomes are significantly worse for those with long-term symptoms. However, surgery may not be the best choice for certain individuals, such as those at high risk or whose symptoms are not caused by vascular compression. Botulinum toxin (BTX) injections can be an effective symptomatic treatment option for specific patient groups, but injections need to be repeated every 3-4 months, and efficacy decreases after a few years of treatment. While some patients might benefit more from ACL reconstruction, there is currently no definitive answer regarding which treatment approach is more beneficial. Additionally, the severity of osteoarthritis should also be taken into account when studying the long-term outcomes of both treatment options. Conclusion: The study concludes that both conservative and surgical treatments for ITBS have their own benefits, but surgical treatment is more effective in achieving long-term pain relief. However, it is important to consider the potential risks and costs associated with each treatment modality and tailor the approach to individual circumstances to achieve the best outcomes. Future research should focus on identifying specific patient predictors for treatment efficacy to guide the selection of the most appropriate treatment approach. Overall, the results of this study contribute to the ongoing advancement of knowledge in the field of ITBS treatment and can guide clinical decision-making for healthcare professionals. DOI:https://doi.org/10.56238/sevened2023.006-014